Relevansi Model Kurikulum Rekonstruksi Sosial dengan Filsafat Rekonstruksionisme George S. Counts: Telaah Pemikiran - Aulia Mustofa; Usvatun Khasanah; Fatiha Amila Sholihah; Khuriyah Khuriyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyzes the relevance of the social reconstruction curriculum model to George S. Counts' philosophy of reconstructionism. The social reconstruction curriculum model encourages students to actively participate in the midst of current societal problems. Meanwhile, George S. Counts' philosophy of reconstructionism views education as the primary tool for reconstructing the social order toward social welfare. This research is motivated by the criticism that the Merdeka Belajar Curriculum is not yet considered fully suitable to be officially adopted as the National Curriculum. This research aims to examine the relevance of the social reconstruction curriculum model as an alternative conceptual framework in the development of the National Curriculum. The method used in this research is library research, which limits the study to only library collections (print and non-print media). The applied analysis technique is Klaus Krippendorff's content analysis. The research findings reveal three main points of relevance between the social reconstruction curriculum model and George S. Counts' philosophy of reconstructionism: relevance based on goals and vision, materials and content, and methods and action. This research found a strong and profound relevance that can serve as an alternative conceptual and philosophical framework for the development of the National Curriculum.